2017
DOI: 10.1186/s12905-017-0456-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic and prognostic features of breast cancer in young women: a series from North of Morocco

Abstract: BackgroundLiterature data reported a higher frequency of breast cancer in young women (BCYW) in developing countries. BCYW is associated with delayed diagnosis, aggressive biology and poor prognosis. However, our knowledge of biological profile, treatment received and outcome of young patients is still limited in Morocco. We propose to analyze clinicopathologic, therapeutic and prognostic features of BCYW among a series of patients native and/or inhabitant of North of Morocco.MethodsWe carried out a retro-pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 47 publications
1
19
2
4
Order By: Relevance
“…Accordingly, different molecular studies of BRCA1/2 have been conducted in hope of understanding their molecular germline alterations in Moroccan HBOC patients. Most of these studies have focused only on breast cancer cases and on young patients due to the fact that breast cancer is described as young women disease in the Arab world and other developing nations like some African and Asian countries [15][16][17]. Moreover, studies that analyzed the molecular profile of BRCA1/2 in HBOC Moroccan patients rarely had ovarian cancer cases in their cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, different molecular studies of BRCA1/2 have been conducted in hope of understanding their molecular germline alterations in Moroccan HBOC patients. Most of these studies have focused only on breast cancer cases and on young patients due to the fact that breast cancer is described as young women disease in the Arab world and other developing nations like some African and Asian countries [15][16][17]. Moreover, studies that analyzed the molecular profile of BRCA1/2 in HBOC Moroccan patients rarely had ovarian cancer cases in their cohort.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study conducted in Egypt between the years 2005 and 2015 in the Oncology Center -Mansoura University, O. Farouk et al demonstrated that three hundred and seventy-nine patients (8.19%) were aged ≤35 years at the time of presentation, the age ranged between 21 and 35 years and the mean age was 31 years [11]. Another significant difference is seen in Morocco, where the prevalence of breast cancer in women younger than 40 years is markedly disparate (24.8%) as shown in a retro-prospective study conducted between the years 2010 and 2015 including 331 infiltrating breast cancer cases [12]. However, Saudi Arabia is found to have concordant results with 4.1% of females younger than the age of 30 years being diagnosed with breast cancer in a 5-year retrospective study [13].…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to other Arabic countries, a hospital-based study conducted in Egypt including 150 patients with breast cancer found that 19% had a familial breast cancer and among those three quarters had a first degree relative with breast cancer [18]. J. Bekkach et al revealed in a 5-year retrospective study in Morocco including 331 subjects with infiltrating breast cancer that 26% of all patients (young and old) had a family history of either breast cancer in a first or second degree relative or ovarian cancer [12]. The presence of breast cancer in the young age group was not always accompanied by the presence of a family history of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Alive patients who were referred to our Clinic between January 2010 to December 2015 were recruited and molecular analysis was carried out in 2017 (33 patients from 82 initially identified). The patients "selection" by delayed molecular analysis can change some characteristics such as family history, metastatic cancer and triple negative breast cancers rates (26% in the initial group Vs. 18.8% in the analyzed group, 12.2% Vs. 3%, and 23% Vs. 30.3%, respectively) [2]. Lastly, our analysis was restricted to BRCA1/2 mutations and did not include large rearrangements nor copy number variations.…”
Section: Discussionmentioning
confidence: 99%
“…From January 2010 to December 2015, a total of 82 young patients (≤ 40 years) with invasive breast carcinoma were referred to the Oncology Clinic AL AMAL in Tangier. Clinico-pathologic, prognostic and therapeutic features of the whole group were previously published [2]. Alive patients were invited to participate in the genetic study and were informed about potential implications of the test.…”
Section: Study Patientsmentioning
confidence: 99%